Teatime birthdays : afternoon-tea celebrations for all ages - Reeves, Lorna (Hoffman Media, 2020)
This collection of 10 afternoon-tea menus includes table settings and recipes idyllic for a range of themes--from a little girl's fairy-inspired party to a Jurassic-themed one for boys to a Parisian-glam Sweet 16, as well as several elegant options for adults. Each set of scones, savories, and sweets has a perfectly paired tea to complement each course, and our tea-steeping guide ensures each infusion is properly prepared. With more than 90 recipes, TeaTime Birthdays will make party-planning simple, and each menu is certain to delight invitees and, especially, the guest of honor.